Proteomic research on diapause-related proteins in the female ladybird, Coccinella septempunctata L. Issue 2 (25th November 2015) - Ren, X.Y.; Zhang, L.S.; Han, Y.H.; An, T.; Liu, Y.; Li, Y.Y.; Chen, H.Y.
Abstract: In the experiments reported here, we used the female ladybird Coccinella septempunctata L. as a model to identify diapause-associated proteins using proteomics technology. Our results indicated that protein expression patterns of diapausing and nondiapausing individuals were highly differentiated. A total of 58 spots showed significant differences in abundance (Ratio > 2 and P < 0.05) according to two-dimensional electrophoresis and GE Image Scanner III analysis. Sixteen protein spots were further investigated using mass spectrometry. Eight proteins were characterized, including chaperones and proteins involved in glucose metabolism, lipid metabolism, and the tricarboxylic acid cycle. Among these proteins, five proteins were upregulated in diapausing female adults, including a chaperone (Symbionin symL), malate dehydrogenase (putative), two proteins linked to lipid metabolism (unknown and conserved hypothetical protein) and phosphoglyceromutase (partial). By contrast, isocitrate dehydrogenase (RH49423p), fumarylacetoacetate hydrolase (AGAP001942-PA), and a putative medium chain acyl-CoA dehydrogenase were downregulated. These results contribute to the understanding of diapause mechanisms of the ladybird C. septempunctata and may suggest methods for improving the application of this natural enemy insect.